2017
DOI: 10.1038/srep41993
|View full text |Cite
|
Sign up to set email alerts
|

MISSA 2.0: an updated synthetic biology toolbox for assembly of orthogonal CRISPR/Cas systems

Abstract: Efficient generation of plants carrying mutations in multiple genes remains a challenge. Using two or more orthogonal CRISPR/Cas systems can generate plants with multi-gene mutations, but assembly of these systems requires a robust, high-capacity toolkit. Here, we describe MISSA 2.0 (multiple-round in vivo site-specific assembly 2.0), an extensively updated toolkit for assembly of two or more CRISPR/Cas systems. We developed a novel suicide donor vector system based on plasmid RK2, which has much higher clonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
15
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 47 publications
6
15
0
1
Order By: Relevance
“…The main reason for this inconsistency in results is that our previous conclusions were based on only one or two T1 plants, and that different promoters were used to drive Cas9. Consistent with this notion, in our previous report on sgRNA targeting the ABI1 gene, the investigation of eight T1 abi1 mutants and two T2 populations for off-target mutations generated similar results to that observed in the present study (Zhang et al, 2017b). It will be interesting to use our egg cell-specific promoter-controlled (EPC) CRISPR/Cas9 system to determine the specificity of GAI-sgRNA1 since its specificity score was 64 relative to the range of 0-100, much lower than that (94) of the sgR-ETC2 (Haeussler et al, 2016;Hsu et al, 2013).…”
Section: High-frequency T-dna Insertions Into Cleavage Sites Of Crispsupporting
confidence: 92%
See 4 more Smart Citations
“…The main reason for this inconsistency in results is that our previous conclusions were based on only one or two T1 plants, and that different promoters were used to drive Cas9. Consistent with this notion, in our previous report on sgRNA targeting the ABI1 gene, the investigation of eight T1 abi1 mutants and two T2 populations for off-target mutations generated similar results to that observed in the present study (Zhang et al, 2017b). It will be interesting to use our egg cell-specific promoter-controlled (EPC) CRISPR/Cas9 system to determine the specificity of GAI-sgRNA1 since its specificity score was 64 relative to the range of 0-100, much lower than that (94) of the sgR-ETC2 (Haeussler et al, 2016;Hsu et al, 2013).…”
Section: High-frequency T-dna Insertions Into Cleavage Sites Of Crispsupporting
confidence: 92%
“…Therefore, it is not strange for the high-frequency off-target 11 / 26 11 / 26 mutations in the CPC off-target site harboring a mismatch in the 8 th nt in the PAM-proximal position ( Figure 1). Similar to this study, our previous investigation involving sgRNA-ABI1 indicated that the off-target sites also harbor a mismatch in the 9 th nt in the PAM-proximal position (Zhang et al, 2017b). The frequency of off-target events was also affected by mismatch identity and could be largely indicated as: rN:dT ≥ rU:dG >> rC:dC >> rA/rG:dA/dG (Doench et al, 2016;Tsai and Joung, 2016;Tycko et al, 2016).…”
Section: High-frequency T-dna Insertions Into Cleavage Sites Of Crispsupporting
confidence: 81%
See 3 more Smart Citations